Mitochondrial Genome Structures and Phylogenetic Analyses of Two Tropical Characidae Fishes - Sun, Cheng-He; Liu, Hong-Yi; Xu, Nan; Zhang, Xiao-Li; Zhang, Qun; Han, Bo-Ping (Frontiers in Genetics, 2021)
The Characidae family contains the largest number of tropical fish species. Morphological similarities make species identification difficult within this family. Here, the complete mitogenomes of two Characidae fish were determined and comparatively analyzed with those of nine other Characidae fish species. The two newly sequenced complete mitogenomes are circular DNA molecules with sizes of 16,701 bp (Hyphessobrycon amandae; MT484069) and 16,710 bp (Hemigrammus erythrozonus; MT484070); both have a highly conserved structure typical of Characidae, with the start codon ATN (ATG/ATT) and stop codon TAR (TAA/TAG) or an incomplete T−−/TA−. Most protein-coding genes of the 11 Characidae mitogenomes showed significant codon usage bias, and the protein-coding gene cox1 was found to be a comparatively slow-evolving gene. Phylogenetic analyses via the maximum likelihood and Bayesian inference methods confirmed that H. amandae and H. erythrozonus belong to the family Characidae. In all Characidae species studied, one genus was well supported; whereas other two genera showed marked differentiation. These findings provide a phylogenetic basis for improved classification of the family Characidae. Determining the mitogenomes of H. erythrozonus and H. amandae improves our understanding of the phylogeny and evolution of fish species.